Institutional Logic of Various Development Actors in Microcredit Program (Case study: Group-Based Microcredit Program (KMBK) in Sukorame Village, Binangun District, Blitar Regency, East Java, Indonesia) - Moch Agus Junaidi; Ratna Dewi Mulyaningtyas (HABITAT, 2020)
The effforts to facilitate community’s participation and encourage their contributions to the decision making process has led to increased development initiatives. Among community development initiatives, the program of Group-Based Microcredit Program (KMBK) has been recognized by development stakeholders as a development approach that offers poor people access to financial services (financial intermediation). In addition, social intermediation in the form of training programs (capacity building) is the key success in eradicating poverty in sustainable development. This study aims to compare the institutional logic of various development actors in the KMBK program in Sukorame Village, Binangun District, Blitar Regency, East Java, Indonesia. This study found that there are differences in institutional logic between development actors in the microcredit program to support sustainable development, namely 'economic logic' and 'development logic'.